Deteriorating Performance of Students of Community School in English - Baral, Parmeshor (Marsyangdi Journal, 2021)
Tremendous attempts have been made to ensure the quality of education and educational status of the students since if performance in the English language is good, it opens the door of the vast ocean of knowledge. Even though community school education in Nepal receives a significant portion of the total national budget, students' performance in those schools is below average, when compared to students in private institutions with limited resources and teachers who receive merger remuneration. This paper attempts to shed light on the causes of poor performance in the English language among Nepalese community school students in Nepal. This is a qualitative study in which assertions are backed up by pieces of evidence. It is based on previous studies about deteriorating English language performance in the world in general, and in Nepal in particular. The study identified student enrolment, motivation and language learning, politicization, lack of teachers’ professional development, and limited exposure to the English language as the major causes of students’ poor performance in English.